The role of IL-38 in intestinal diseases - its potential as a therapeutic target - Wang, Qiang; Ma, Linna; An, Caiping; Wise, Steven G.; Bao, Shisan (Frontiers in Immunology, 2022)
IL-38, an anti-inflammatory cytokine, is a key regulator of homeostasis in host immunity. Intestinal immunity plays a critical role in defence against pathogenic invasion, as it is the largest surface organ and the most common entry point for micro-organisms. Dysregulated IL-38 activity is observed in several autoimmune diseases including systemic lupus erythematosus and atherosclerosis. The protective role of IL-38 is well illustrated in experimental colitis models, showing significantly worse colitis in IL-38 deficient mice, compared to wildtype mice. Moreover, exogenous IL-38 has been shown to ameliorate experimental colitis. Surprisingly, upregulated IL-38 is detected in inflamed tissue from inflammatory bowel disease patients, consistent with increased circulating cytokine levels, demonstrating the complex nature of host immunity in vivo. However, colonic IL-38 is significantly reduced in malignant tissues from patients with colorectal cancer (CRC), compared to adjacent non-cancerous tissue. Additionally, IL-38 expression in CRC correlates with 5-year survival, tumour size and differentiation, suggesting IL-38 plays a protective role during the development of CRC. IL-38 is also an independent biomarker for the prognosis of CRC, offering useful information in the management of CRC. Taken together, these data demonstrate the role of IL-38 in the maintenance of normal intestinal mucosal homeostasis, but that dysregulation of IL-38 contributes to initiation of chronic inflammatory bowel disease (resulting from persistent local inflammation), and that IL-38 provides protection during the development of colorectal cancer. Such data provide useful information for the development of novel therapeutic targets in the management of intestinal diseases for more precise medicine.